Empowering entrepreneurship competences through socialization of educational entrepreneurship for elementary school teachers in Jakarta - Arita Marini; Desy Safitri; Ika Lestari; Musril Zahari; Rossi Iskandar; Ajat Sudrajat; Sri Nuraini; Taufik Rihatno; Yustia Suntari; Maratun Nafiah; Rosinar Siregar (Universitas Muhammadiyah Malang, 2022)
Partner of this international collaboration of community service is Konstanz University of Applied Sciences in Germany, Prof. Dr. Christian von Lübke, to be invited to collaborate in giving socialization about educational entrepreneurship for elementary school teachers in the province of Jakarta Indonesia. The target of this community service is elementary school teachers in the Province of Jakarta Indonesia. The socialization of educational entrepreneurship for elementary school teachers was done to develop entrepreneurship competences of elementary school teachers in the Province of Jakarta Indonesia, the solution undertaken was socialization of educational entrepreneurship. The methods used in conducting this international collaboration of community service were cooperative learning, problem-based learning, and giving assignments. This socialization was conducted through video conferences in the form of learning activities to improve the competence in educational entrepreneurship for elementary school teachers in the province of Jakarta Indonesia. The socialization of educational entrepreneurship given is related to developing entrepreneurial interest with appropriate learning activity programs. This international collaboration of community service was conducted at elementary schools in the Province of Jakarta Indonesia because those elementary schools are regularly empowered by Universitas Negeri Jakarta. Based on evaluation measurement, teachers’ interest in entrepreneurship education reached 86,75 % and the average satisfaction level of participants were 94%.